Students’ Obstacles on Autonomous English Learning - Andi Dian Rahmawan (Journal of English Language Teaching and English Linguistics, 2020)
This study attempts to give teachers a perspective regarding what problems students face during the process of learning English material by employing the Autonomous Learning. The researcher used Pragmatics as the subject of learning to observe the process of Autonomous Learning during one semester. This is a descriptive qualitative research in which 7 students of English Education of PGRI University were employed as the subjects of this study. Those students are the most active ones in class. After they conducted a series of learning process autonomously, they were expected to fill the questionnaire as the data source to reveal the basic need of the students that they are expecting from the teachers. Then the data would be explained descriptively. It is expected that the teachers are going to have some new perspectives regarding the autonomous learning, which is related to the students’ problems. What they want the teachers to do and what the teachers should provide are two fundamental considerations. This study reveals that the autonomous learning does not mean that the students learn the material fully autonomously. Bigger than that, the students still need the presence of the teachers as the agent of autonomous learning.